Critical reflection on the ESL teacher's subjectivity. Issue 1 (2nd January 2017) - Nam, Jihyun
Abstract: This study explores the possibility of raising the author's own critical awareness as an ESL teacher by reflecting critically on his subjectivity involved in the implementation of critical literacy in the reading classroom, especially examining not just his thoughts and feelings but also his teaching practices. It highlights discrepancies between his expectations and realities, and conflicts between his own beliefs. It also highlights not just effective aspects of his teaching, which show his contribution to enhancing dialogue among students and their engagement with critical social practices, but also less-effective aspects of his teaching, which show his failure to push participants for more information and his distortions of participants' statements. Further, the study demonstrates the need for encouraging teachers to reflect critically on themselves as transformative beings.